Pengaruh Trend Fashion, Life Style, Brand Image Terhadap Keputusan Pembelian dan Niat Beli Ulang pada Dunia Hijab L-Scraft Lamongan - Elsa Eka Pratiwi; Indira Shofia Maulida; Puguh Cahyono; Diah Ayu Novitasari (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
In today’s modern era there are a lot of muslim women who wear hijab with various models, motifs, trends that adjust to fashion trend, life style, brand image of today muslim women. The purpose of this study is to provide an understanding of marketing management and to find out the influence of trend fashion, life style, brand image on purchase decisions and repurchase intentions in the world of L-scraft Lamongan hijab. The sample taken was 90 and used the questionnaire distribution technique with the help of the SPSS data processing application. Which states positive and significant results means that there is a influence between the three variables on purchase decisions and repurchase intentions.